A Two-week IXPE Monitoring Campaign on Mrk 421 - Maksym, W. Peter; Liodakis, Ioannis; Saade, M. Lynne; Kim, Dawoon E.; Middei, Riccardo; Gesu, Laura Di; Kiehlmann, Sebastian; Matzeu, Gabriele; Agudo, Iván; Marscher, Alan P.; Ehlert, Steven R.; Jorstad, Svetlana G.; et al. (Institute of Physics Publishing, 2026)
X-ray polarization is a unique new probe of the particle acceleration in astrophysical jets made possible through the Imaging X-ray Polarimetry Explorer. Here we report on the first dense X-ray polarization monitoring campaign on the blazar Mrk 421. Our observations were accompanied by an even denser radio and optical polarization campaign. We find significant short-timescale variability in both X-ray polarization degree and angle, including an ∼90° angle rotation about the jet axis. We attribute this to random variations of the magnetic field, consistent with the presence of turbulence but also unlikely to be explained by turbulence alone. At the same time, the degree of lower-energy polarization is significantly lower and shows no more than mild variability. Our campaign provides further evidence for a scenario in which energy-stratified shock-acceleration of relativistic electrons, combined with a turbulent magnetic field, is responsible for optical to X-ray synchrotron emission in blazar jets.